The Cambridge history of the book in Britain. (Cambridge)
6 c. (1. c. xx, 827 s., [48] s. tıpkıbasım ; 2. c. xxiv, 615 s., [81] s. tıpkıbasım ; 3. c. xxiv, 743 s., [62] s. tıpkıbasım ; 4. c. xxvii, 891 s., [32] s. tıpkıbasım ; 5. c. xxvi, 1020 s., [48] s. tıpkıbasım ; 6. c. xvii, 808 s.)